2023
DOI: 10.3390/antiox12040818
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicles of Toxigenic Clostridioides difficile Affect the Metabolism of Liver HepG2 Cells

Abstract: Clostridioides difficile infection (CDI) appears to be associated with different liver diseases. C. difficile secretes membrane vesicles (MVs), which may be involved in the development of nonalcoholic fatty liver disease (NALFD) and drug-induced liver injury (DILI). In this study, we investigated the presence of C. difficile-derived MVs in patients with and without CDI, and analyzed their effects on pathways related to NAFLD and DILI in HepG2 cells. Fecal extracellular vesicles from CDI patients showed an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…However, exposure of intestinal cells to C. difficile EVs induces a dose-dependent proinflammatory and cytotoxic response [ 125 ]. Caballano et al found that despite the absence of TcdA and TcdB in C. difficile EVs, their epithelial toxicity involves the expression of apoptosis-related genes (CASP3), an effect that was not distinguished in non-toxigenic strains of C. difficile [ 128 ].…”
Section: Extracellular Vesicles In Other Medically Important Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, exposure of intestinal cells to C. difficile EVs induces a dose-dependent proinflammatory and cytotoxic response [ 125 ]. Caballano et al found that despite the absence of TcdA and TcdB in C. difficile EVs, their epithelial toxicity involves the expression of apoptosis-related genes (CASP3), an effect that was not distinguished in non-toxigenic strains of C. difficile [ 128 ].…”
Section: Extracellular Vesicles In Other Medically Important Bacteriamentioning
confidence: 99%
“…B. cereus EVs induce TNFα production in monocytes and cause enterocyte lysis [ 127 ]. Exposure of intestinal and hepatic cells to C. difficile EVs induces the production of IL-1β, IL-6, IL-8, and MCP-1 [ 125 , 128 ].…”
Section: Immunological Effects Of Bacterial Extracellular Vesiclesmentioning
confidence: 99%